Opposing regulation and roles for PHD3 in lung dendritic cells and alveolar macrophages. Issue 4 (1st October 2017) - Tavernier, Simon J.; Vanlangenakker, Nele; Vetters, Jessica; Carmeliet, Peter; Janssens, Sophie; Lambrecht, Bart N.
Abstract : HDM‐induced PHD3 in lung DCs does not contribute to asthma development, but is required for alveolar MFs to reconstitute an irradiated niche. Abstract : The prolyl hydroxylase domain‐containing enzymes (PHDs) are important metabolic sensors of the cell and its environment, which might be employed to alert cells of the immune system. These enzymes regulate the expression of the hypoxia inducible factor (HIF) isoforms and NF‐κB, crucial transcription factors controlling cellular metabolism and inflammation. PHD/HIF signaling is activated in the allergic lung and is proposed as a potential druggable pathway. Here, we investigated the regulation and role of the PHD isoforms in CD11c‐expressing dendritic cells (DCs) and macrophages (Mϕ), sensors of the environment and crucial antigen‐presenting cells in the pathogenesis of asthma. Although PHD2 and PHD3 were expressed in baseline, stimulation with house dust mite (HDM) allergen, hypoxia, and TLR4 ligands induced the expression of PHD3 in DCs. Conditional deletion or overexpression of PHD3 in CD11c hi cells had minor effects on DCs and alveolar Mϕ biology in steady state. However, when put into competition with wild‐type counterparts in mixed chimeric mice, alveolar Mϕ uniquely required PHD3 for optimal reconstitution of the alveolar space. Using genetic and chemical approaches, we were unable to find a clear role for PHD3 or the other PHD isoforms in DCs in asthma development. These data show cell‐specific competitive advantage of PHD3 expression in antigen‐presenting cells, but question whether therapeutic manipulation of PHDs in DCs would offer therapeutic benefit in asthma.